John Lennon : all I want is the truth : a photographic biography - Partridge, Elizabeth (New York, NY : Viking, 2005)
The story of one of rock's biggest legends, from his birth during a 1940 World War II air raid on Liverpool, through his turbulent childhood and teen years, to his celebrated life writing, recording, and performing with the Beatles and beyond
Give peace a chance (1969) -- Mendips (1940-1952) -- Rock 'n' Roll (1952-1956) -- Two of us (1957) -- Hold on (1957-1958) -- Make show! (1958-1961) -- Breaking out (1961-1963) -- Beatlemania (1963-1965) -- Trapped (1965-1967) -- Crashing big-time (1967-1969) -- JohnandYoko (1969-1971) -- Slipping and sliding (1971-1975) -- Househusband in search of himself (1975-1980) -- John's legacy
Includes bibliographical references (p. 215-219) and index
Keywords: Lennon, John, -- 1940-1980 -- Juvenile literature; Rock musicians -- England -- Biography -- Juvenile literature; Juvenile materials